2010
DOI: 10.1007/s12035-010-8154-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics and Pathogenic Mechanisms for the Severe Ciliopathies: Insights into Neurodevelopment and Pathogenesis of Neural Tube Defects

Abstract: Meckel-Gruber syndrome (MKS) is a severe autosomal recessively inherited disorder characterized by developmental defects of the central nervous system that comprise neural tube defects that most commonly present as occipital encephalocele. MKS is considered to be the most common syndromic form of neural tube defect. MKS is genetically heterogeneous with six known disease genes: MKS1, MKS2/TMEM216, MKS3/TMEM67, RPGRIP1L, CEP290, and CC2D2A with the encoded proteins all implicated in the correct function of prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 118 publications
1
51
0
1
Order By: Relevance
“…A number of centriolar satellite proteins, such as PCM1 and the ciliopathy proteins Cep290 and Bardet-Biedl syndrome protein 4 (BBS4) cooperate in the formation of the primary cilia (Kim et al, 2008;Lopes et al, 2011;Stowe et al, 2012), an organelle that has only recently been appreciated as a crucial signalling hub for a number of pathways, which include Wnt and sonic hedgehog (Logan et al, 2011). Recent work has demonstrated that a number of proteins involved in the DNA damage response (DDR) also function during ciliogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…A number of centriolar satellite proteins, such as PCM1 and the ciliopathy proteins Cep290 and Bardet-Biedl syndrome protein 4 (BBS4) cooperate in the formation of the primary cilia (Kim et al, 2008;Lopes et al, 2011;Stowe et al, 2012), an organelle that has only recently been appreciated as a crucial signalling hub for a number of pathways, which include Wnt and sonic hedgehog (Logan et al, 2011). Recent work has demonstrated that a number of proteins involved in the DNA damage response (DDR) also function during ciliogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 lists these differential diagnoses, and the chromosomal regions (obtained from the UCSC genome browser, http://genome.ucsc.edu) in which the causative genes/ candidate loci lie (Bendavid et al, 2010;Logan et al, 2011;Roessler and Muenke, 2010;Wallis and Muenke, 2000;Yu and Patel, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The sequence of the DHCR7 gene ruled out Smith-Lemli-Opitz syndrome (SLO). We did not sequence the gene responsible for Hydrolethalus syndrome (HYLS1), as this syndrome almost invariably includes polyhydramnios, a 'key-hole shaped' foramen magnum, severe hydrocephalus and pre-axial (rather than post-axial) polydactyly of the lower limbs (Honkala et al, 2009); likewise the pathognomonic features of Meckel syndrome, which include occipital encephalocele, bilateral renal cystic dysplasia, hepatic duct proliferation, fibrosis and cysts, were not present (Chen, 2007;Logan et al, 2011). Pallister-Hall syndrome, caused by mutations in the GLI3 gene, was excluded as the foetus did not have a hypothalamic hamartoma, bifid epiglottis, imperforate anus, or the renal abnormalities that are characteristic of this syndrome, and the family history was indicative of autosomal recessive rather than autosomal dominant inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…No (34) Bardet-Biedl Syndrome 12 615989 BBS12 Yes (23) Bardet-Biedl Syndrome 13 615990 BBS13/MKS1 Yes (15,35) Meckel Syndrome 1 249000 Id. No (36) Bardet-Biedl Syndrome 14 615991 BBS14/CEP290/NPHP6 Yes (15) Leber congenital amaurosis 611755 Id. No (37) Joubert Syndrome 5 610188 Id.…”
Section: Intraflagellar Transportmentioning
confidence: 99%